Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0038223
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Cell Line HC-AFW1 Derived from a Pediatric Hepatocellular Carcinoma

Abstract: Current treatment of paediatric hepatocellular carcinoma (HCC) is often inefficient due to advanced disease at diagnosis and resistance to common drugs. The aim of this study was to generate a cell line derived from a paediatric HCC in order to expand research in this field. We established the HC-AFW1 cell line from a liver neoplasm of a 4-year-old boy through culturing of primary tumor specimens. The cell line has been stable for over one year of culturing and has a doubling time of 40 h. The tumour cells hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In fact HepG2 cells show deletion of 116 and HC-AFW1 a deletion of 49 amino acids. 15,16 Successful silencing of β-catenin or Yap gene in these two cell lines (Figure 2A) led to a notable decrease in cell proliferation and a significant increase in apoptosis as well (Figure 2B-C). However, more pronounced and synergistic anti-growth effect was observed following simultaneous silencing of β-catenin and Yap genes in HepG2 and HC-AFW1 cells (Figure 2B-C).…”
Section: Resultsmentioning
confidence: 93%
“…In fact HepG2 cells show deletion of 116 and HC-AFW1 a deletion of 49 amino acids. 15,16 Successful silencing of β-catenin or Yap gene in these two cell lines (Figure 2A) led to a notable decrease in cell proliferation and a significant increase in apoptosis as well (Figure 2B-C). However, more pronounced and synergistic anti-growth effect was observed following simultaneous silencing of β-catenin and Yap genes in HepG2 and HC-AFW1 cells (Figure 2B-C).…”
Section: Resultsmentioning
confidence: 93%
“…Using CD133 as a biomarker is also limited in terms of predicting clinicopathological significance and prognosis in HCC patients. In addition to CD133, some other cell surface molecules have been considered potential CSC markers in HCC patients, including CD90, CD44, and EpCAM [44,45]. Ma et al found that CD133 + ALDH + cells were significantly more tumorigenic than CD133 + ALDH − or CD133 − ALDH − cells both in vitro and in vivo [46].…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines and culture conditions HC-AFW1 was derived from a 5-year old boy suffering from HCC [11]. Huh7, a cell line derived from a differentiated aHCC, was obtained from the Japanese Collection of Research Bioresources (JCRB0403).…”
Section: Methodsmentioning
confidence: 99%
“…Viability was measured using MTT assay as described above. Sensitization was further investigated combining sorafenib with cisplatin (3.9 mg/ml) and doxorubicin (4.0 mg/ml), using IC50 doses as previously described [11].…”
Section: Sensitization To Sorafenibmentioning
confidence: 99%
See 1 more Smart Citation